2021
DOI: 10.3390/ijerph18041452
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Realist Review of Group Psychological First Aid for Humanitarian Workers and Volunteers

Abstract: Humanitarian workers are at an elevated risk of occupational trauma exposure and its associated psychological consequences, and experience increased levels of anxiety, depression, and post-traumatic stress disorder (PTSD) compared to the general population. Psychological first aid (PFA) aims to prevent acute distress reactions from developing into long-term distress by instilling feelings of safety, calmness, self- and community efficacy, connectedness and hope. Group PFA (GPFA) delivers PFA in a group or team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
(113 reference statements)
0
25
0
Order By: Relevance
“…We believe a peer-led team approach has merit, and is supported by the literature on PFA for groups. 10,16,17…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We believe a peer-led team approach has merit, and is supported by the literature on PFA for groups. 10,16,17…”
Section: Discussionmentioning
confidence: 99%
“…11,17 It is the team that provides the support to each other through validation of shared reactions, social connection, and through role modelling to guide constructive self-help behaviours, including seeking help. 16,17 It is not the facilitator who directly delivers this support. This avoids any suggestion of a victim versus hero dynamic, and is empowering for the team.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, although the HCWs who elected to participate in our symptom monitoring service (and consented for their data to be used in research) reported relatively low levels of distress, for which the cause is difficult to determine, this result does not negate the critical importance of implementing psychological support programs for HCWs. Additionally, while our goal regarding the assessment of mental health symptoms in the current study was to describe our sample and document their mental health functioning, it should be noted that there remains a need for research that rigorously evaluates the effectiveness of PFA using similar measures (Corey et al, 2021;Yue et al, 2020).…”
Section: Mental Health and Psychological Functioning Of Hcwsmentioning
confidence: 99%